Korespondencinė analizė kaip chronologinis metodas - Kačkutė, Rūta (Archaeologia Lituana, 2012)
Šiame straipsnyje bus kalbama apie korespondencinę analizę (angl. correspondent analyses) – archeologijos moksle taikomą tyrimą, kuris yra pagrįstas seriacijos metodu. Pažodinis termino „correspondent analyses“ vertimas į lietuvių kalbą būtų „atitikties tyrimas“, tačiau, nesant nusistovėjusios lietuviškos terminijos, ir siekdama aiškumo pasirinkau terminą, kuris asocijuojasi su angliškuoju....USE OF THE CORRESPONDENCE ANALYSIS IN ARCHEOLOGYRūta KačkutėSummaryAbstract. This article aims at introducing correspondence analysis, the technique applied in the science of archaeology, and at showing how it can be used in chronological research. Correspondence analysis rests upon the seriation method that has been in use by the archaeological scientists since the late 19th century. The seriation method basically draws upon the theoretical statement that the development of material culture is of a continuous character and guided by fashion and/or functionally-determined mechanisms that make the repetition of the elements follow a double-lens-shaped road over time (Madsen, 1989 a, p. 10). There are several ways of doing seriation. Correspondence analysis is one of the techniques successfully applied in archaeological research. The technique was developed in France and broadly recognised by Scandinavian archaeologists, but still not very much in use by archaeologist in the Baltic States. The article illustrates the use of correspondence analysis for detecting chronology of Early Roman Iron Age graveyard ceramics. The correspondence analysis performed rests on KVARK, the software developed by T. Madsen. The article explains how this program works and how convenient it is for chronological and social studies....